2007
DOI: 10.1111/j.1440-0960.2007.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Signet‐ring cell carcinoma of the gallbladder with skin metastases

Abstract: Cutaneous metastasis from gallbladder cancer is extremely rare. We present a case of signet-ring cell carcinoma of the gallbladder metastatic to the skin in a 38-year-old man. The skin nodules on the face, scalp and perianal area occurred approximately 1 year after the resection of the neoplasm. Skin metastases from gastrointestinal cancers are usually detected around surgical scars or on the abdominal wall, especially in the periumbilical region, and rarely present at other sites. Multiple imaging studies rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…There are only rare reports of peritoneal 7 or pleural 9 mesothelioma involving the skin usually because of cutaneous extension or distant metastasis 10 with one report of pleural mesothelioma involving chest wall scars 9 . However, it is not uncommon for gastrointestinal malignancies to extend around surgical scars 20 . Cutaneous involvement by visceral cancers has been reported to occur in 0.7–9% of patients and is generally a late occurrence in the disease process.…”
Section: Resultsmentioning
confidence: 99%
“…There are only rare reports of peritoneal 7 or pleural 9 mesothelioma involving the skin usually because of cutaneous extension or distant metastasis 10 with one report of pleural mesothelioma involving chest wall scars 9 . However, it is not uncommon for gastrointestinal malignancies to extend around surgical scars 20 . Cutaneous involvement by visceral cancers has been reported to occur in 0.7–9% of patients and is generally a late occurrence in the disease process.…”
Section: Resultsmentioning
confidence: 99%
“…Signet ring cell carcinoma of gallbladder with metastasis is extremely rare but this patient had metastasis in celiac lymph node. [11] Ultrastructurally, signet ring cell carcinoma of gallbladder reveals mucin vacuoles and the intracytoplasmic lumina, some of which are cystically dilated. In contrast, well-differentiated adenocarcinoma recapitulates the ultrastructure of normal surface epithelium although columnar cell predominates; the narrow and dark-staining pencil-like cells are also present.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to what has been reported in the literature previously 3. Krunic et al 5 reported a case of signet ring cell adenocarcinoma of gall bladder with multiple metastases to the skin in the form of nodules on the skin, scalp and perianal area. Multiple metastases to bone were also seen.…”
Section: Discussionmentioning
confidence: 99%